“Terpasung Tak Terasa” (Melihat Eksistensi Politik Perempuan HTI) - Elly Triantini, Zusiana (Unisia, 2012)
Reformation has brought about various models of thought, including fundamentalist Islamic thoughts, one of them being Hizbut Tahrir Indonesia (HTI). HTI offers various concepts that are controversial, including the concept of khilafah as an alternative to the collapsed political and governmental systems of Indonesia. One of its controversial concepts is that of political role of women which is gender biased and combines sociological and theological domains. This paper reveals that such a bias is caused by the method of interpretation of texts, which is literal or textual, by which the texts have to be understood as it is explicitly written, not implicitly. This tends to reject other understandings that are logical and contextual, using historical interpretation. Keywords: reformation, HTI, women, gender-biased.